Fibroblast growth factor receptor 2 overexpression is predictive of poor prognosis in rectal cancer patients receiving neoadjuvant chemoradiotherapy. Issue 12 (30th September 2014) - Li, Chien-Feng; He, Hong-Lin; Wang, Jaw-Yuan; Huang, Hsuan-Ying; Wu, Ting-Fe; Hsing, Chung-Hsi; Lee, Sung-Wei; Lee, Hao-Hsien; Fang, Jui-Lung; Huang, Wen-Tsung; Chen, Shang-Hung
Abstract : Aims: Neoadjuvant concurrent chemoradiotherapy (CCRT) followed by surgery is an increasingly used therapeutic strategy for advanced rectal cancer, but risk stratification and final outcomes remain suboptimal. Recently, the oncogenic role of the fibroblast growth factor/fibroblast growth factor receptor (FGFR) signalling pathway has been recognised; however, its clinical significance in rectal cancer has not been elucidated. In this study, we identify and validate targetable drivers associated with the FGFR signalling pathway in rectal cancer patients treated with CCRT. Methods: Using a published transcriptome of rectal cancers, we found FGFR2 gene significantly predicted response to CCRT. The expression levels of FGFR2, using immunohistochemistry assays, were further evaluated in 172 rectal cancer specimens that had not received any treatment. Expression levels of FGFR2 were statistically correlated with major clinicopathological features and clinical survival in this valid cohort. Results: High expression of FGFR2 was significantly related to advanced pretreatment tumour (p=0.022) and nodal status (p=0.026), post-treatment tumour (p<0.001) and nodal status (p=0.004), and inferior tumour regression grade (p<0.001). In survival analyses, high expression of FGFR2 was significantly associated with shorter local recurrence-free survival (p=0.0001), metastasis-free survival (MeFS; p=0.0003) and disease-specific survival (DSS; p<0.0001). Notably, high expression of FGFR2 was independently predictive of worse outcomes for MeFS (p=0.002, HR=5.387) and DSS (p=0.004, HR=4.997). Conclusions: High expression of FGFR2 is correlated with advanced tumour stage, poor therapeutic response and worse survival in rectal cancer patients receiving neoadjuvant CCRT. These findings indicate that FGFR2 is a prognostic factor for treating rectal cancer.